Effects of Dietary Protein Levels on Haemato-biochemical Response and DNA: RNA ratio of Pabda, Ompok bimaculatus (Bloch, 1794) - Jena, A. K.; Biswas, Pradyut; Arambam, Kalpana; Parhi, Janmejay; Pandey, P. K. (Fishery Technology, 2019)
Five iso-energetic semi-purified diets with varying levels of crude protein viz., P25 (25.10%), P30 (29.93%), P35 (35.28%), P40 (39.73%) and P45 (44.49%) were fed to Pabda, Ompok bimaculatus fingerlings (average weight 3.29Â±0.01 g) in triplicate groups (11 healthy fish per replicate) for a period of 60 days to study the haemato-biochemical parameters and nucleotide concentration of the fish. Fish were stocked in indoor plastic tanks, provided with 500 l of aerated freshwater in each tank. Each group was fed to satiation twice a day for 60 days. Significant differences were observed in haematobiochemical parameter, RNA concentration and RNA:DNA ratios with different dietary protein levels. These parameters showed an increasing trend with an increase in the dietary protein levels up to P35 diets (p<0.05), decreased thereafter. Fish fed with low and high level protein diets showed lesser values of red blood cells, haemoglobin content, haematocrit and total plasma protein when compared with optimum protein level (35.28%). Moreover, the highest glucose level in plasma was observed in fish fed with the lowest protein diet whereas, no significant difference was observed in their WBC counts. Significantly higher (p<0.05) muscle RNA and RNA: DNA ratio was found in P35 fed group diets. All these parameters were negatively affected by the further increase in protein level in the diet. It may be concluded that the dietary protein level influences the haemato-biochemical response and nucleotide concentration of O. bimaculatus, which showed an increasing trend with increase in dietary protein to optimum level (P35) and decreased after that.